The impact of operational risk events on company reputation through FSA's Final Notices - Atayev, Kemal (2014)
In this research paper I study the effects of operational risk events on the share prices of the financial services firms. Unlike other studies the information is delivered to the market through FSA's Final Notices. The loss amount however is also untraditional as I use the penalty set by the FSA as the loss amount. I analyse the abnormal returns of 23 companies from the US and the UK within the time period of 2002-2013. I found that there is a significant negative impact by the those operational risk events on the share prices within a window of -5 and +5 days around the event date. In addition the country of enlistment also had significant results as companies from the US had greater negative impact than those from the UK. The relative size of the penalty also proved to have significant impact as the firms with larger relative loss size had greater negative impact. In regression analysis the penalty also showed significant results as it was shown that the penalty seems to drive the severity of the impact. Overall the Final Notices issued by the FSA do indeed carry similar weight to the traditional information announcements even though when compared to the traditional research the negative reaction is not as lasting as the reaction of that research. However the size of the penalty proved to be a very good indicator of the severity of the operational risk event especially when there was no actual monetary loss.